Linearized approach for predicting loss coefficients in entrance region flows of purely viscous non-Newtonian fluids in an annular duct - Mishra I.M.; Mishra P. (My University, 2025)
The linearization technique for predicting loss coefficients in laminar entrance region flows for Newtonian fluids is extended to inelastic non-Newtoni. © 1977.